The Role of Customary Leaders in Resolving Domestic Disputes (Case Study of the Towani Tolotang Community in Amparita District, Sidenreng Rappang Regency) - Nur Syamsuryana Mustari; Rusdaya Basri; Zainal Said; Rahmawati; Sunuwati (UIN Siber Syekh Nurjati Cirebon, 2026)
Family is the smallest social unit that plays a a crucial role in maintaining social harmony and welfare. However, domestic conflicts between spouses are inevitable due to differences in character, interests, and socio-economic pressures. In the context of Indonesia’s plural society, dispute resolution is not only conducted through formal legal mechanisms but also through customary practices rooted in local wisdom. This study aims to analyze the role of customary leaders in resolving household disputes within the Towani Tolotang community in Sidenreng Rappang Regency, South Sulawesi. This topic remains relatively underexplored in existing literature, particularly in the context of social transformation and the increasing influence of formal law. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through in-depth interviews, observation, and documentation involving customary leaders, married couples, and community figures. The findings reveal that customary leaders (uwa) play a central role as mediators, resolving domestic conflicts by emphasizing cultural values such as siri’ (honor), pacce (empathy), and lempu’ (honesty). The dispute resolution mechanism is carried out through structured yet flexible customary mediation stages that prioritize deliberation, moral guidance, and reconciliation before reaching a final decision. The study also finds that this mechanism is relatively effective, as most domestic disputes are resolved through customary mediation without leading to divorce. This helps strengthen family harmony and social cohesion within the community. In conclusion, the role of customary leaders remains relevant as a form of living law that preserves family integrity and sustains local cultural values amid modernization. Keywords: Customary Leaders; Towani Tolotang; Household Disputes; Customary Mediation; Living Law